Understanding the Impact of Soil Characteristics and Field Management Strategies on the Degradation of a Sprayable, Biodegradable Polymeric Mulch - Cuyler K. Borrowman; Raju Adhikari; Kei Saito; Stuart Gordon; Antonio F. Patti (Agriculture)
The use of non-degradable plastic mulch has become an essential agricultural practice for increasing crop yields, but continued use has led to contamination problems and in some cropping areas decreases in agricultural productivity. The subsequent emergence of biodegradable plastic mulches is a technological solution to these issues, so it is important to understand how different soil characteristics and field management strategies will affect the rate at which these new materials degrade in nature. In this work, a series of lab-scale hydrolytic degradation experiments were conducted to determine how different soil characteristics (type, pH, microbial community composition, and particle size) affected the degradation rate of a sprayable polyester–urethane–urea (PEUU) developed as a biodegradable mulch. The laboratory experiments were coupled with long-term, outdoor, soil degradation studies, carried out in Clayton, Victoria, to build a picture of important factors that can control the rate of PEUU degradation. It was found that temperature and acidity were the most important factors, with increasing temperature and decreasing pH leading to faster degradation. Other important factors affecting the rate of degradation were the composition of the soil microbial community, the mass loading of PEUU on soil, and the degree to which the PEUU was in contact with the soil.